Improvement of the tunable wettability property of poly(3-alkylthiophene) films - Lin, Peng (Langmuir : the ACS journal of surfaces and colloids, 2009)
The surface wettability properties of poly(3-alkylthiophene) (P3AT) can be reversibly switched between hydrophobic and hydrophilic states by a low-voltage electrochemical approach. The switching processes corresponding to the oxidation and deoxidation processes of the polymer films have been systematically studied. The tunable region of the contact angle of the polymer films is dependent on the type of dopant, and the biggest effect was induced by SO4(2-) doping, which changes the contact angle for about 30 degrees. The tunable amplitude of the contact angle has been substantially enlarged by coating the polymer film on a substrate patterned with micrometer-sized posts, which shows a static contact angle of 147.4 degrees at neutral state and 62.2 degrees at oxidized state. It is envisaged that the polymer films have potential applications as low cost disposable wettability switches in microfluidics and contact-printing technology